1982
DOI: 10.1007/bf02693740
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of sexual dimorphism in primates: Ecological and size variables

Abstract: The effects of a series o f ecological and size factors on the degree of sexual dimorphism in body weight

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
3

Year Published

1989
1989
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(134 citation statements)
references
References 21 publications
1
130
3
Order By: Relevance
“…With this point in mind, we decided to further investigate the data by analyzing the sexes separately. Whereas some previous authors have suggested that papionin males may be better suited for detailing differences in anatomy (51-54), a number of studies commonly suggest that males are more variable in many features (55)(56)(57)(58)(59) and, by extension, probably less valuable in taxonomic and phylogenetic studies. Instead, many authors commonly use females as the optimal phenotype for interspecific analysis (60,61).…”
Section: Figmentioning
confidence: 99%
“…With this point in mind, we decided to further investigate the data by analyzing the sexes separately. Whereas some previous authors have suggested that papionin males may be better suited for detailing differences in anatomy (51-54), a number of studies commonly suggest that males are more variable in many features (55)(56)(57)(58)(59) and, by extension, probably less valuable in taxonomic and phylogenetic studies. Instead, many authors commonly use females as the optimal phenotype for interspecific analysis (60,61).…”
Section: Figmentioning
confidence: 99%
“…At the population and species level, positive allometry can be proximately manifest, for example, if there are different amounts of genetic variation in males and females and the sex with more additive genetic variation for body size has a stronger evolutionary response to selection (Leutenegger & Cheverud 1982). Similarly, a natural selection gradient (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Others have criticized the use of correlational values derived from measurements on individuals to then make inferences about body size in species (Chown and Gaston, 1997). The last assumption may be particularly problematic because of primate sexual dimorphism and the annual variations in body size that occur in many Malagasy strepsirhines (Atsalis, 1999;Clutton-Brock, 1985;Ganzhorn and Schmid, 1998;Kappeler, 1991;Leutenegger and Cheverud, 1982;Plavcan and van Schaik, 1997;Smith and Cheverud, 2002). Some researchers have questioned the unimodal, right-skewed distribution that is inherent to the OBS model (Jones and Purvis, 1997;Kozlowski, 1996;Lovegrove and Haines, 2004).…”
Section: Introductionmentioning
confidence: 99%